Hitler's Secret War In South America, 1939-1945 : German Military Espionage and Allied Counterespionage in Brazil - Hilton, Stanley E., 1940- (Book collections on Project MUSE., 1981)
In the years that followed World War II, hundreds of books were written about different aspects of that unprecedented conflict, but the details of the "secret war" in the West were slow to appear, in large part because of agreements concluded in 1945 between the American and British governments that forbade the release of information on covert operations, especially in the field of cryptanalysis, that is, the interception and decrypting of enemy radio communications. A curtain of silence thus descended on that vital phase of the Allied struggle against the European Axis. From the point of view of Germany's clandestine war effort, the situation was slightly different because the Reich had lost the war; even so, the archives of the Abwehr, as the Amt/Ausland of the Oberkommando der Wehrmacht, or Foreign Department of the Armed Forces High Command, was known, could not be located, and it was logically assumed that the Germans had destroyed them before the war ended.